Position-Selective Growth of WO3 Nanosheets for NH3 Gas Sensors - Megersa, Daba Deme; Cho, Hyeon Ho; Kim, Youngho; Gudena, Gutema Teshome; Lee, Jaeyeong; Bae, Jong Seong; Chae, Sudong; Yu, Hak Ki (Crystal Growth and Design, 2023)
In this study, chemical vapor deposition of WO3 via graphene-catalyzed thermal transport is utilized to prepare position-selective WO3 micro/nanostructures. The effects of growth temperature and oxygen concentration on the structure, morphology, surface chemical states, and electrical properties are studied. The growth temperature and oxygen concentration are found to alter the resulting morphology and electrical properties. The combined application of high temperature and high oxygen concentration results in porous WO3 nanosheets with active surfaces. The prepared nanosheets are utilized for room-temperature NH3 gas sensing, and they exhibit good sensitivity, response time, and recovery time.
Keywords: Chemical vapour deposition; Gas-sensors; High oxygens; Highest temperature; Micronanostructure; Oxygen concentrations; Selective growth; Surface chemical state; Temperature concentration; Thermal transport